If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -3)(-2x + -14) = 0 Reorder the terms: (-3 + 6x)(-2x + -14) = 0 Reorder the terms: (-3 + 6x)(-14 + -2x) = 0 Multiply (-3 + 6x) * (-14 + -2x) (-3(-14 + -2x) + 6x * (-14 + -2x)) = 0 ((-14 * -3 + -2x * -3) + 6x * (-14 + -2x)) = 0 ((42 + 6x) + 6x * (-14 + -2x)) = 0 (42 + 6x + (-14 * 6x + -2x * 6x)) = 0 (42 + 6x + (-84x + -12x2)) = 0 Combine like terms: 6x + -84x = -78x (42 + -78x + -12x2) = 0 Solving 42 + -78x + -12x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6'. 6(7 + -13x + -2x2) = 0 Factor a trinomial. 6((1 + -2x)(7 + x)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5Subproblem 2
Set the factor '(7 + x)' equal to zero and attempt to solve: Simplifying 7 + x = 0 Solving 7 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + x = 0 + -7 x = 0 + -7 Combine like terms: 0 + -7 = -7 x = -7 Simplifying x = -7Solution
x = {0.5, -7}
| (-6x+3)(2x-14)= | | (-3x+9)(4x-2)= | | 6*9-9y=-54 | | c^2=2c+35 | | 9.7/5.9 | | y^2+100=20y | | (x+1)(x-1)(x-8)=0 | | 4z=18-26 | | (6x^3-1x^2+1)/(2x+1) | | (6x-54)/5=-3x | | 30=6r-24+3t | | 7-(-5)+4-(-3)= | | 12=-2m | | -x-(1/7)=x+(1/6)+(2/7) | | 1/6x^2=48 | | 4w+13=61 | | x+2(x-4)=100 | | 1/3x^2=48 | | (275)(x-373)(.444)=(100)(x-295)(4.184) | | 1/3x^2=54 | | Y=3/2*0-6 | | -.25x+6x-2=20 | | 8/x+8=7/x-4 | | 7t^2+3=10t | | 0.18(y-8)+0.14y=0.16y-0.05(60) | | (3/9)+(x/3)=7/9 | | 10-(3x-4)=8-4x | | (x^2)-2x-48=0 | | -10.4x^2+132x+332=750 | | -3(x-7)-6(3x-3)=-22(x-1)+9 | | (x^3)-4(x^2)-9x+36=0 | | x-(-5)=-5 |